Development of Geogebra Assisted Teaching Materials Surface Area of Roying Objects - Arie Wahyuni; St Budi Waluya; Nuriana Rachmani Dewi; Destia Wahyu Hidayati (International Conference on Science, Education, and Technology, 2022)
One of the learning activities is teaching materials. Teaching materials are very helpful for students when they have difficulty understanding the learning material. The purpose of this research is to produce teaching materials assisted by geogebra material on the surface area of ​​rotating objects that are valid and practical. This research method uses the 4D development research method, but the researchers only arrived at the 3D stage of defining, designing, and developing. The research instrument used a validation sheet of 2 material experts and 1 media expert. The results of the study obtained that teaching materials assisted by geogebra material on the surface area of ​​rotating objects were valid and practical. The average acquisition of expert validation is 3.90, which means that the average score of expert validation is in the good category and is feasible to be tested. The results of the questionnaire response analysis and direct interviews, it can be concluded that these teaching materials help students learn the material because they are considered easy to understand and lead students to find problem solving using geogebra.